2005
DOI: 10.1021/jp044979c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Testing and Characterization of Doped TiO2 Active in the Peroxidation of Biomolecules under Visible Light

Abstract: Doped TiO2 samples using different preparative procedures were synthesized using either urea or thiourea leading to N- or S-doped TiO2. Photocatalytic peroxidation and oxidation (mineralization) of phosphatidylethanolamine (PE) lipid with doped TiO2 were carried out under light irradiation lambda > 410 nm. The formation of conjugated double bonds in PE molecules was followed to detect the formation of peroxy radicals (peroxidation index) under light excitation (lambda > 410 nm) when doped TiO2 was used. The ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 34 publications
6
158
0
7
Order By: Relevance
“…Recently, we have reported the mechanism of the damage induced by TiO 2 photocatalysis on the bilayer cell-envelope of Escherichia coli in several studies [20][21][22][23]. Other groups working in the disinfection field have also addressed the mechanism of disinfection [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported the mechanism of the damage induced by TiO 2 photocatalysis on the bilayer cell-envelope of Escherichia coli in several studies [20][21][22][23]. Other groups working in the disinfection field have also addressed the mechanism of disinfection [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…6, traces 3) and 4) show that higher loadings of Cu did not lead to a faster bacterial inactivation kinetics due to their higher Cu-content, but that the bacterial inactivation was essentially due to Cu-ions. Some recent reports have addressed bacterial inactivation mediated by TiO 2 doped by N and S under light [58,59]. The faster bacterial inactivation kinetics induced by the co-sputtered CuOx-TiO 2 -PET samples compared to N, S-doped TiO 2 is partly due to the effective binding of CuOx/TiO 2 with E. coli.…”
Section: Bacterial Inactivation Kinetics In the Dark And Under Light mentioning
confidence: 99%
“…The pattern of the Cu and Ti sputtered on PET is complicated by the surface diffusion controlling the mass transport of Cu (II)/Cu (I) and Ti on PET [58,59]. Fig.…”
Section: X-ray Photoelectron Spectroscopy (Xps) and Evidence For Redomentioning
confidence: 99%
“…These species tend to retard the phase transition of anatase to rutile and crystallite growth. Recently, phosphate/titanium dioxides have been obtained through different preparative * E-mail: K.elghniji@yahoo.fr routes entailing either surface modification of titanium oxide or hydroxide hydrate by anions, such as phosphates or sulfates [1][2][3][4][5][6][7][8] or hydrolysis of TiO 2 from corresponding titanium alkoxides in presence of phosphoric acid [9][10][11][12]. Ramadan et al [13] reported a study on titanium dioxide obtained from the hydrolysis of titanium ethoxide and phosphate by impregnation with ammonium hydrogen phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…The authors argued that the bidentated phosphate groups HPO 2− 4 were persistent up to 800°C, indicating the stability of these groups within the titanium oxide structure to high temperatures. Gong [14] identified two species on the surface, namely the bridging bidentate surface complex (TiO) 2 The number of papers on phosphorus/phosphate-TiO 2 is undergoing an exponential increase. As it often occurs in case of a rapidly growing subject, a certain degree of confusion due to conflicting evidences and interpretations is present in the literature.…”
Section: Introductionmentioning
confidence: 99%